2020
DOI: 10.1002/cam4.2870
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and its associations with the clinicopathologic characteristics of diffuse large B‐cell lymphoma

Abstract: Microsatellite instability (MSI) has been investigated as a prognostic and predictive factor for chemotherapy in colorectal cancer and has recently been demonstrated to be predictive of the PD‐1/PD‐L1 checkpoint blockade response in various solid tumors. However, MSI status in diffuse large B‐cell lymphomas (DLBCLs) has not been thoroughly explored. This study investigated MSI status in DLBCLs and analyzed the associations between MSI and clinicopathologic characteristics and clinical outcomes. Ninety‐two case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, recent analyses of NGS data showed that MSI-H in non-Hodgkin lymphoma, including DLBCL, is either extremely rare (<1%) or not a feature of these tumors [ 4 7 ]. In contrast to those reports, a study using a commercial MSI kit, based on eight mononucleotide repeat markers and two pentanucleotide repeat markers, identified MSI-H and microsatellite instability–low (MSI-L) in 3% (3/92) and 10% (9/92) of DLBCLs, respectively [ 9 ]. According to the authors, patients with MSI-H DLBCL tended to have a better prognosis than those with microsatellite stable DLBCL, although the difference was not significant [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent analyses of NGS data showed that MSI-H in non-Hodgkin lymphoma, including DLBCL, is either extremely rare (<1%) or not a feature of these tumors [ 4 7 ]. In contrast to those reports, a study using a commercial MSI kit, based on eight mononucleotide repeat markers and two pentanucleotide repeat markers, identified MSI-H and microsatellite instability–low (MSI-L) in 3% (3/92) and 10% (9/92) of DLBCLs, respectively [ 9 ]. According to the authors, patients with MSI-H DLBCL tended to have a better prognosis than those with microsatellite stable DLBCL, although the difference was not significant [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to those reports, a study using a commercial MSI kit, based on eight mononucleotide repeat markers and two pentanucleotide repeat markers, identified MSI-H and microsatellite instability–low (MSI-L) in 3% (3/92) and 10% (9/92) of DLBCLs, respectively [ 9 ]. According to the authors, patients with MSI-H DLBCL tended to have a better prognosis than those with microsatellite stable DLBCL, although the difference was not significant [ 9 ]. They also reported that MSI-L DLBCL was associated with a poor response to chemotherapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSI and MMR status have not been defined in various hematologic malignancies, but deficient status is seen in approximately 9% in cHL, 40 8% in PMBCL, 83 and 0.3% to 3.2% in DLBCL. 84,90 Their association with response to checkpoint blockade is currently unknown in lymphoma as no patients with lymphoma were represented in the trials involving MSI-H/dMMR cancers.…”
Section: Msi and Mmrmentioning
confidence: 99%